1999
DOI: 10.1007/s002329900576
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intracellular Ca 2+ by CFTR in Chinese Hamster Ovary Cells

Abstract: In cystic fibrosis, the mutation of the CFTR protein causes reduced transepithelial Cl(-) secretion. As recently proposed, beside its role of Cl(-) channel, CFTR may regulate the activity of other channels such as a Ca(2+)-activated Cl(-) channel. Using a calcium imaging system, we show, in adenovirus-CFTR infected Chinese Hamster Ovary (CHO) cell monolayers, that CFTR can act as a regulator of intracellular [Ca(2+)](i) ([Ca(2+)](i)), involving purino-receptors. Apical exposure to ATP or UTP produced an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This ATP receptor is also linked to the mobilisation of [Ca 2+ ] i and through pharmacological characterisation it appears to be a P2Y 2 and/or P2Y 4 receptor [178]. Exposure to ATP or UTP on the apical side of confluent CHO cell monolayers produced an increase in [Ca 2+ ] i [407]. It was also shown that functional expression of human CFTR in the plasma membrane of CHO cells infected with adenovirus regulated the increase in intracellular Ca 2+ produced by ATP released from the cells.…”
Section: Female Reproductive Organsmentioning
confidence: 99%
“…This ATP receptor is also linked to the mobilisation of [Ca 2+ ] i and through pharmacological characterisation it appears to be a P2Y 2 and/or P2Y 4 receptor [178]. Exposure to ATP or UTP on the apical side of confluent CHO cell monolayers produced an increase in [Ca 2+ ] i [407]. It was also shown that functional expression of human CFTR in the plasma membrane of CHO cells infected with adenovirus regulated the increase in intracellular Ca 2+ produced by ATP released from the cells.…”
Section: Female Reproductive Organsmentioning
confidence: 99%
“…However, the pleiotropic effects due to CFTR dysfunctions and observed on epithelial ion transport in CF largely exceed the impairment of the Cl Ϫ channel function and may be related to other regulatory properties of CFTR. Indeed, in addition to functioning as a cAMP-regulated Cl Ϫ channel, CFTR has been shown to regulate several ion channels by notably activating P2YR subsequent to ATP release (Schwiebert et al, 1995;Urbach and Harvey, 1999).…”
Section: The Cystic Fibrosis (Cf) Transmembrane Conductance Regulatormentioning
confidence: 99%
“…However, the pleiotropic effects due to CFTR dysfunctions and observed on epithelial ion transport in CF largely exceed the impairment of the Cl Ϫ channel function and may be related to other regulatory properties of CFTR. Indeed, in addition to functioning as a cAMP-regulated Cl Ϫ channel, CFTR has been shown to regulate several ion channels by notably activating P2YR subsequent to ATP release (Schwiebert et al, 1995;Urbach and Harvey, 1999).Extracellular nucleotides are important signaling moleThis work was supported by institutional grants from the Centre National de la Recherche Scientifique (CNRS), the Institut National de la Santé et de la Recherche Médicale (INSERM), and by the French association Vaincre la Mucoviscidose. B.M.…”
mentioning
confidence: 99%
“…Purinergic agonists are essential for many specialized physiological functions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In cystic fibrosis (CF), 1 ATP and a related triphosphate nucleotide, UTP, stimulate epithelial chloride (Cl Ϫ ) channels alternative to CFTR via purinergic receptors (11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%